PELATIHAN PEMBUATAN PUPUK ORGANIK CAIR DENGAN BIO AKTIVATOR DI KENAGARIAN PANCUNG TABA KECAMATAN BAYANG UTARA KABUPATEN PESISIR SELATAN - Ediwirman Ediwirman (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2022)
Increased production in agriculture affects the income and welfare of farmers. One of the factors that determine agricultural production is the availability of sufficient nutrients for plants through fertilization. Fertilizers given in addition to chemical fertilizers (inorganic) can also be given liquid organic fertilizer (POC). Liquid organic fertilizer is essential in improving soil fertility and increasing the availability of nutrients needed by plants. This service aims to make farmers understand the importance of liquid organic fertilizer and develop it independently as an alternative fertilizer by utilizing local resources. The service is carried out in socialization and training in the manufacture of liquid organic fertilizers. Liquid organic fertilizer uses local raw materials derived from animal manure and agricultural waste such as livestock manure and husks enriched with bio activators such as EM4 and Trico G. The service has shown that farmers understand the use of liquid organic fertilizers and are technically able to prepare them properly. Good. Liquid organic fertilizer of good quality can be obtained through a fermentation process for 14 days and then applied repeatedly to various cultivated plants.